The Role of The Principle of Freedom of Contract in the Implementation of International Trade Law - Muhammad Panji Mahardika; Rifqi Nur Fakhrurozi (DE'RECHTSSTAAT, 2025)
This summary examines the crucial role of the principle of "freedom of contract" in international trade, which is an integral part of the global economy. This principle provides businesses with the freedom to negotiate contract terms, fostering fair and efficient agreements. However, its implementation faces challenges such as cultural differences and legal systems that can impact contract integrity. This study aims to determine the crucial role of the principle of "freedom of contract" in international trade. This study uses a normative approach. The results show that the principle of freedom of contract plays a crucial role in building business bridges in the international market. By providing flexibility in negotiations, increasing trust between parties, and providing an efficient dispute resolution mechanism, freedom of contract enables businesses to adapt to the dynamics of the global market. Despite these challenges, a sound understanding of applicable law and an awareness of the risks can help businesses leverage this principle to achieve success in international trade. Thus, freedom of contract is not merely a legal principle but also a strategic tool that can connect various business entities worldwide.